Budget impact analysis of baricitinib for treatment of alopecia areata: A Saudi hospital perspective - A. Alshahrani; S. Al-Aqeel; M. Alshahrani; S. Alqahtani; S.T. Alhawwashi; M.S. Al-Nasser; M. Zaitoun (Saudi Pharmaceutical Journal)
Objectives: To perform a budget impact analysis (BIA) of the adoption of baricitinib for the management of alopecia areata (AA) by a Saudi public sector payer. Methods: A BIA model was developed to calculate the expected financial impact under two scenarios: the baseline scenario, which reflects the current mix of treatments without baricitinib, and the projected scenario, in which baricitinib is adopted. The model assumed that patients with severe AA and those with mild-to-moderate AA who did not respond to other treatments were eligible for baricitinib treatment. The model input was based on published evidence, expert opinions, and the Saudi Expert Consensus Statement on the Diagnosis and Management of AA. Results: Assuming a hypothetical total eligible population of 368 patients received different AA treatments over the 12-months study period. The aggregated 5-years cost in the baseline scenario was SR 5,836,616. Upon the introduction of baricitinib as an alternative treatment for severe AA, the projected aggregated budget impact was SR 7,473,138. Sensitivity analysis showed that the results were most sensitive to AA prevalence, percentage of severe AA, and predicted market share for baricitinib over the 5-year time horizon. Conclusion: The addition of baricitinib to formularies is likely to increase the cost impact from a government hospital perspective. However, this addition expands the treatment options for patients with AA and may result in improved outcomes. Future cost-effectiveness analyses are recommended to estimate the cost per incremental improvement in the outcomes.